2017
DOI: 10.1051/0004-6361/201730885
|View full text |Cite
|
Sign up to set email alerts
|

K2-106, a system containing a metal-rich planet and a planet of lower density

Abstract: Aims. Planets in the mass range from 2 to 15 M ⊕ are very diverse. Some of them have low densities, while others are very dense. By measuring the masses and radii, the mean densities, structure, and composition of the planets are constrained. These parameters also give us important information about their formation and evolution, and about possible processes for atmospheric loss. Methods. We determined the masses, radii, and mean densities for the two transiting planets orbiting K2-106. The inner planet has an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 94 publications
6
61
2
Order By: Relevance
“…We felt a homogeneous analysis was warranted because the results in the literature were reported by different groups using different procedures to determine the stellar parameters and to mitigate the effects of timecorrelated noise in the radial-velocity data. For example, K2-106b was reported by Guenther et al (2017) to have an iron mass fraction of 80 +20 −30 %, while Sinukoff et al (2017) concluded that the composition was compatible with that of the Earth (35% iron). For this work, we combined all the previously published datasets, used the parallaxes from Gaia Data Release 2 (Gaia Collaboration et al 2018) to refine the stellar parameters, and employed a Gaussian Process framework to disentangle planetary radial velocity signals from cor-related noise.…”
Section: Introductionmentioning
confidence: 99%
“…We felt a homogeneous analysis was warranted because the results in the literature were reported by different groups using different procedures to determine the stellar parameters and to mitigate the effects of timecorrelated noise in the radial-velocity data. For example, K2-106b was reported by Guenther et al (2017) to have an iron mass fraction of 80 +20 −30 %, while Sinukoff et al (2017) concluded that the composition was compatible with that of the Earth (35% iron). For this work, we combined all the previously published datasets, used the parallaxes from Gaia Data Release 2 (Gaia Collaboration et al 2018) to refine the stellar parameters, and employed a Gaussian Process framework to disentangle planetary radial velocity signals from cor-related noise.…”
Section: Introductionmentioning
confidence: 99%
“…TESS also enables the discovery of multi-planet systems for which both mass and radius can be precisely measured. Because such planets orbit the same star, differences in mean density and atmospheric structure among planets belonging to the same system can be ascribed mainly to differences in planetary mass and orbital separation (see, e.g., Guenther et al 2017;Prieto-Arranz et al 2018). This greatly simplifies modeling of their past evolution history, thus constraining how these planets formed (Alibert et al 2005;Alibert & Benz 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These planets have the advantage that due to their short periods, their masses and radii can be determined with high accuracy. Currently known transiting ultrashort-period planets (USPs) include CoRoT-7b (Léger et al 2009), 55 Cnc e (Winn et al 2011), Kepler-10b (Batalha et al 2011), Kepler-78b (Sanchis-Ojeda et al 2013, WASP-47e (Dai et al 2015;Sinukoff et al 2017a), KOI 1843.03 ), K2-106 (Guenther et al 2017), and HD3167b (discovery: Vanderburg (2016), characterization: Gandolfi et al (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Other potentially interesting objects to search for the signatures of volcanism and an exosphere using optical transmission spectroscopy are K2-106 (Guenther et al 2017) and HD3167 b (Vanderburg 2016;Gandolfi et al 2017;Christiansen et al 2017). What makes these objects interesting is that their densities are higher than that of 55 Cnc e. K2-106 b and HD3167 b have a density of 13.1 −3.6 +5.4 and 8.00 +1.10 −0.98 g cm −3 , respectively.…”
Section: Introductionmentioning
confidence: 99%